The Issues of Unclaimed Properties in Malaysia - Wan Yusoff, Wan Zahari; Sulaiman, Muhammad Azwan (Journal of Social Transformation and Regional Development, 2021)
Unclaimed property in Malaysia has become one of the more hotly debated issues. So far unclaimed property value estimated to reach billions of Ringgit. This is a big number, and, if issues stay no action has taken, it will affect not only the society but also economic and national development. If the efficient property management system had to be set up it will have undoubtedly a positive impact. Therefore, there is a need to take a drastic action to find a comprehensive solution and alternatives for solving this issue. Hence, an effective asset management and an efficient estate planning towards unclaimed property must be practiced to ensure a smooth operation of the property management. Generally, unclaimed property is divided into two main categories. Firstly, the inherited estate from a deceased that is not claimed by the heirs and another one is the property the owner of which cannot be traced or missing, known as al-Mafqud in Islamic law. In this paper, the researcher has focused on the occurrence of unclaimed property in the context of missing persons. The results of this study are based on data gathered through a grounded theory from few agencies such as the Malaysian Civil and Shariah Courts, Small Estate Distribution Unit in the District Land Office and Amanah Raya Berhad as well as the heirs of missing persons. The information of missing person's heirs collected from Royal Malaysia Police (RMP) and the information clarified as confidential.  In general, the result shows that, there are for factors contributed to the issues of unclaimed properties in Malaysia; legislation, social status, behavior and the strength and weaknesses of related agency should be given consideration.  This results are expected to be catalyst to further action by the government to solve the issue of unclaimed property in Malaysia and concurrently contribute to enhance the quality of property management based on highest and best use concept.